2022
DOI: 10.1016/j.rceng.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for clinical deterioration in patients admitted for COVID-19: A case-control study

Abstract: Introduction There is controversy regarding the best predictors of clinical deterioration in COVID-19. Objective This work aims to identify predictors of risk factors for deterioration in patients hospitalized due to COVID-19. Methods design Nested case-control study within a cohort. Setting: 13 acute care centers of the Osakidetza-Basque Health Service. Participants: Patients hospitalized for COVID-19 with clinical deterioration—defined as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…These findings were consistent with a recent studies conducted in China and United States, where no association was found between co-morbidities and ICU admission [2,17]. Consistent findings were found in another study conducted in Spain, in which COPD and Asthma were not correlated with ICU admission [3]. Furthermore, another cross-sectional analytical study conducted at a tertiary care center in Nepal similarly found that co-morbidities were not associated with the outcome of COVID-19 [18].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings were consistent with a recent studies conducted in China and United States, where no association was found between co-morbidities and ICU admission [2,17]. Consistent findings were found in another study conducted in Spain, in which COPD and Asthma were not correlated with ICU admission [3]. Furthermore, another cross-sectional analytical study conducted at a tertiary care center in Nepal similarly found that co-morbidities were not associated with the outcome of COVID-19 [18].…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that patient presenting with tachypnea during the time of hospital admission were 15.5 times more likely to be admitted in ICU. These findings was alike with several studies where the respiration rate was found to be significantly associated with ICU admission [ 3 , 14 , 17 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations